Mali - Improving Learning in Public Schools - Mohan, P.C. (World Bank, Washington, DC, 2012)
The overall objective of this Learning and Innovation Credit (2000-2003: US$3.8 million) was to further develop and assess the merits of bilingual education in Mali, in terms of financial and educational sustainability. The project was designed at a time when the education system was facing the following problems: (i) low enrollments, including gender and regional imbalances; (ii) poor learning results in primary schools; (iii) low efficiency in public education; (iv) poor accessibility to education for all children; (vi) proliferation of models for community involvement in schooling; and (vii) central management. To achieve its objective, the approach taken was to introduce a bilingual education model - pedagogie convergente - in six languages as the basis for introducing curricular revisions, producing textbooks based on the changed curricula, testing teaching and learning materials, testing student achievement at the end-of-project to determine the model's efficacy, and building community partnerships to elicit local support for introducing the model at the primary education level.